(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
This paper presents results of micromorphological studies of seeds surface ultrastructure of P. oleracea s.l. (Portulacaceae) and its intraspecies diversity. According to the results of our research the following nine taxa of the P. oleracea s. l. from the studied region were noted: P. daninii, P. granulatostellulata, P. nitida, P. oleracea s. str., P. papillatostellulata, P. rausii, P. trituberculata, P. macrantha, P. sardoa. Two last taxa are new for Ukrainian flora. The most widespread morphotype in the studied region is P. granulatostellulata (50.4 % of investigated specimens), less common is P. papillatostellulata (20.6 %), significantly less – P. macrantha and P. sardoa (7.8 % each), very rare in the region as well as in Europe are P. nitida, P. oleracea s. str. and P. rausii. It was found that the widespread as well as in the studied region and in Ukraine are P. granulatostellulata and P. papillatostellulata; some taxa, e.g. P. nitida, P. oleracea and P. rausii are rare as well as in the region and in Europe in general. It was established that in some localities from the studied complex were presented plants of several morphotypes (e.g., two – P. granulatostellulata + P. papillatostellulata; P. rausii + P. trituber-culata or three – P. granulatostellulata + P. papillatostellulata + P. sardoa) or even several morphotypes on one individual (e.g., P. granulatostellulata + P. papillato-stellulata; P. macrantha + P. trituberculata). The original scanning electron microscopy photographs of seeds surface ultrastructure of the studied morphotypes and key for its determination are suggested. Conclusions: Intraspecific diversity of P. oleracea complex (nine morphotypes) was established in Zhytomyr Polissia and Right-Bank Forest Steppe zone of Ukraine. On studied territory was noted an essential dominance of intraspecific taxa of the complex with seed surface with different microsculptures (P. granulatostellulata, P. macrantha, P. papillatostellulata, P. rausii, P. sardoa, P. trituberculata) in contrast morphotypes to with smooth one (P. nitida and P. oleracea). The results of study indicate the complexity of P. oleracea s.l. and, accordingly, different views on the status of taxa. Further research of the complex in different regions of the country to establish its composition, natural-species differentiation, evolution and reconstruction of the ways of introduction and distribution is relevant.